PRSA Ethical Principles Representation in The Intern Film: Representasi Prinsip Etika PRSA dalam Film The Intern - ervin restu; Ainur Rochmaniah (Academia Open, 2025)
General Background: Professional ethics in public relations are essential for sustaining organizational credibility, stakeholder trust, and responsible communication practices. Specific Background: Films often portray workplace communication and professional conduct, providing material for analyzing ethical public relations standards. Knowledge Gap: Existing studies primarily focus on ethical violations or organizational settings, while limited research examines cinematic portrayals of ethical public relations principles using structured semiotic approaches. Aims: This study examines the representation of Public Relations Society of America (PRSA) ethical principles in the film The Intern (2015) using Charles Sanders Peirce’s semiotic analysis. Results: The findings show three PRSA ethical indicators represented through dialogue, visual symbols, and narrative interactions. Free Flow of Information is reflected in transparent communication and employee involvement. Disclosure of Information appears through responsible client communication and problem-solving processes. Professional competency development is illustrated through leadership mentoring and employee guidance within organizational settings. Novelty: This study applies Peirce’s semiotic framework to interpret ethical public relations representation in cinematic media by focusing on symbolic and narrative elements. Implications: The findings demonstrate that films can serve as educational references for understanding public relations ethics and professional values while highlighting the importance of cultural context in interpreting ethical communication practices presented in Western workplace narratives. Highlights: Transparent Organizational Communication Practices Are Symbolized Through Narrative and Visual Elements. Responsible Client Interaction Is Depicted Through Structured Problem-Solving Behavior. Leadership Mentoring Scenes Illustrate Competency Development Within Organizational Settings. Keywords: Prsa Ethics, Semiotic Analysis, Public Relations Communication, Film Representation, Professional Ethics